The distributional impact of public services in European countries - Rolf Aaberge; Audun Langørgen; Petter Lindgren (Statistics Norway, Research Department, 2013)
The purpose of this paper is to study the impact of including the value of public health care, longterm care, education and childcare on estimates of income inequality and financial poverty in 23 European countries. The valuation of public services and the identification of target groups rely on group-specific accounting data for each of the 23 countries. To account for the fact that the receipt of public services like education and care for the elderly is associated with particular needs, we introduce a theory-based common equivalence scale for European countries, termed the needsadjusted EU scale (or NA scale). Even though the ranking of countries by estimates of overall inequality and poverty proves to be only slightly affected by the choice between the conventional EU scale and the NA scale, poverty estimates by household types are shown to be significantly affected by the choice of equivalence scale.
Keywords: D31; I10; I20; I32; 330; Income distribution; Poverty; Public services; In-kind transfers; Needs adjustment; Equivalence scales